Knowledge and Determinants of Health Consequences of Cigarette Smoking Among Vietnamese Adults, 2015. (July 2019) - Minh Dao, An Thi; Thi Thu Nguyen, Huong; Kim, Giang Bao; Phan, Hai Thi; Van Nguyen, Huy; Doan, Huyen Thu; Luong, Khue Ngoc; Nguyen, Lam Tuan; Van Hoang, Minh; Pham, Nga Thi Quynh; Nguyen, Quan The
Background . Vietnam was one of 16 countries that implemented the second round of the GATS (Global Adult Tobacco Survey) in 2015. Aims . To assess knowledge and determinants of health consequences of different types of cigarette smoking among Vietnamese adults. Methods. A cross-sectional study among adults aged 15 years combined with using 15% of the master sample from the national sampling frame of the population and housing census was conducted. Multilevel analysis using Poisson regression was undertaken. Results . Knowledge on the health consequences of cigarette smoking has not significantly improved in the GATS-2015. Adults believe that active smoking had more of an impact on health than secondhand smoking and 24.5% and 43% of them answered that smoking light and e-cigarettes, respectively, causes less harm than regular cigarettes, and 17.3% and 18.1% of adults are not aware of the difference between them, respectively. Conclusion . Household and community's role had little impact in the adult knowledge of smoking health consequences. It is necessary to disseminate information on the "other tobacco product" and to improve public knowledge on specific health consequences, to enhance household and community's role in conveying health education messages to individuals.